Internet Data Consumption During Synchronous Teaching-from-Home Period at Sampoerna University - Muhammad Agni Catur Bhakti; Wandy Wandy; Ajeng Nindi Noviarini (STMIK Budi Darma, 2022)
Since the beginning of Covid-19 in Jakarta, synchronous teaching with Internet communication technology and asynchronous teaching supported by the Learning Management System (LMS) have been adopted at Sampoerna University (SU). Synchronous teaching that initially used a web-based conference technology was later changed to using a communication platform that the University has subscribed to. Lecturers were provided with 15GB (15,360MB) of data per month to support these teaching activities. This research aimed to analyze whether the Internet data quota provided by the Government was sufficient to support the teaching process during this research period. This research used a quantitative method, recorded primary data for three months, and descriptive data with non-probability sampling. It was discovered that only 9,281.34MB of data was being used (60.43%) and still had 6,078.66MB (39.57%) remaining. The conclusion that can be drawn was that the Internet quota provided by the Government was adequate to cover one month of synchronous teaching for three courses with three credits each.